Sulfonated poly(ether sulfone)/poly(vinylidene fluoride) hybrid membrane for vanadium redox flow battery. (June 2017) - Liu, Shibin; Meng, Xiangcai; Wang, Jing; Xu, Jianwei
Sulfonated poly(ether sulfone)/poly(vinylidene fluoride) (SPES/PVDF) blends are prepared and employed as the separator for vanadium redox flow battery (VRB) to evaluate the vanadium ions permeability and cell performance. The SPES/PVDF membranes exhibit dramatically vanadium ions permeability and cell performance compared with pristine SPES and Nafion115 membrane. The vanadium ion permeability of SPES/PVDF membrane is 1 order of magnitude lower than that of Nafion115 membrane. The low-cost composite membrane exhibits a better performance than Nafion115 membrane at the same operating condition. VRB single cell with SPES/PVDF membrane shows significantly lower capacity loss, higher coulombic efficiency (>98%) and higher energy efficiency (>84%) than that with Nafion115 membrane. In the self-discharge test, S0.7 P0.3 membrane shows twice longer duration in the open circuit decay than that with Nafion115 membrane. With all the good properties and low cost, the SPES/PVDF membrane is expected to have excellent commercial prospects as an ion exchange membrane for VRB systems.